Robotic breast surgery: the pursue for excellence in treatment and satisfaction – a review - Clarke, Paula; Pires, Douglas de Miranda; Sá, Nayara Carvalho de; Cavalcante, Jessica Moreira; Oliveira, Fernanda Silveira de (Mastology, 2020)
Introduction: Nipple sparing mastectomy (NSM) with immediate reconstruction is an option for the treatment of breast cancer or for risk-reducing surgery. This technique offers good aesthetic results without compromising oncological safety. Robotic nipple sparing mastectomy (RNSM) was first described in 2015 and has been executed in various centers ever since, but the costeffectiveness and oncological safety of this technique are still questioned. Objectives: The primary aim of this study was to critically review the literature and discuss the feasibility, advantages and limitations of robotic breast surgery. Methods: Search in PubMed database for publications related to “robotic breast surgery”. Selection and review of relevant articles, and analysis of results from these studies. Results: Our search comprised the period between 2015 and 2019. The rates of complications were low and the learning curve is apparently rapid, though there is still a lack of data involving cost-effectiveness. Conclusions: RNSM with immediate reconstruction is a great advance in the surgical treatment for breast cancer. Cost-effectiveness and oncological safety must still be accessed through randomized clinical trials.